Dear Prudence : liberating lessons from Slate.com's beloved advice column - Lavery, Daniel M. (HarperOne, an imprint of HarperCollinsPublishers, 2023)
"Based on the long-running SLATE advice column, a collection of the most eye-opening, illuminating, and provocative installments during Daniel M. Lavery's tenure as the titular Prudence"--